Bimbingan Kelompok Dengan Teknik Problem Solving Dalam Meningkatkan Motivasi Belajar Siswa Kelas XI.1 Di SMAN 4 Tana Toraja - Hiskiawati; Sisilia Tiku; Lidya Sallata; Fitri Tri Intani Pali'pangan; Hesli Filadelfia (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This study aims to determine the effect of group guidance with problem solving techniques in increasing the learning motivation of class XI.1 students at SMAN 4 Tana Toraja. The method used in this research is quantitative approach with experimental design. The sample used was 30 students from class XI.1 who were purposively selected. Group guidance intervention was conducted for 6 meetings with a focus on the application of problem solving techniques in overcoming academic problems faced by students. Data were collected using a learning motivation questionnaire that had been tested for validity and reliability. The results of data analysis showed a significant increase in students' learning motivation after being given group guidance with problem solving techniques. Based on the results of the study, it can be concluded that group guidance with problem solving techniques is effective in increasing students' learning motivation.